2014
DOI: 10.1002/2013jf003064
|View full text |Cite
|
Sign up to set email alerts
|

An approximate solution to the flow field on vegetated intertidal platforms: Applicability and limitations

Abstract: Tidal wetland evolution is governed by interactions between topography, vegetation, and the flow field. Aiming to provide an appropriate hydrodynamic tool within a long‐term geomorphic model of vegetated wetlands, we describe an approximate procedure to model the depth‐averaged flow field on vegetated intertidal platforms. The procedure is tested by a qualitative comparison with laboratory experiments and quantitatively comparing with a numerical model, focusing on the influence of spatial variations in fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In contrast to this positive effect at the small scale, the formation of turbulence around vegetation patches can reinforce wave impact, largely preventing plant colonization at a larger spatial scale (such scale depends on the neighbouring vegetation patches). This long-range negative effect has been confirmed by previous studies based on models and field observations on hydrodynamic conditions next to vegetation patches in intertidal salt marshes [31,59]. Taken together, the short-range facilitation and long-range inhibition are coupled and self-reinforced by the colonization and growth of plants, thus exhibiting a clear SDF.…”
Section: (B) Scale-dependent Feedbackssupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast to this positive effect at the small scale, the formation of turbulence around vegetation patches can reinforce wave impact, largely preventing plant colonization at a larger spatial scale (such scale depends on the neighbouring vegetation patches). This long-range negative effect has been confirmed by previous studies based on models and field observations on hydrodynamic conditions next to vegetation patches in intertidal salt marshes [31,59]. Taken together, the short-range facilitation and long-range inhibition are coupled and self-reinforced by the colonization and growth of plants, thus exhibiting a clear SDF.…”
Section: (B) Scale-dependent Feedbackssupporting
confidence: 82%
“…These contrasting plant performances can be explained by scale-dependent feedbacks. Physical stress caused by wave impact is usually the limiting factor for colonization and growth of plants in tidal front areas [59]. It has been repeatedly observed that the protection from neighbouring established plants can effectively ameliorate such an impact [31], making local plant-plant facilitation the prime mechanism underlying the enhanced performance of S. mariqueter within the vegetation patches.…”
Section: Resultsmentioning
confidence: 99%
“…). This can be expected as the flow field on the marsh platform is frictionally dominated due to the high friction exerted by the vegetation present (e.g., Van Oyen et al , ). Taken together, our field measurements demonstrate the importance of marsh channel geometry for tidal and storm surge propagation in marshes.…”
Section: Discussionmentioning
confidence: 99%
“…In tidal studies where this assumption is commonly made, the external forcing is that of a periodic tidal wave, and Λ∼ UC f . Several studies have shown that this linearization performs well relative to fully nonlinear flow across simple and complex domains (Marani et al, ; Van Oyen et al, , ), although significant errors do arise from spatially variable friction and very shallow flows. An important property of this linear model is that it conforms to Poisson's equation, ∇ 2 h w =Λ/( gH 2 ) ∂H / ∂t (Rinaldo et al, ; note that ∂H / ∂t signifies the changing spatially averaged tidal water depth).…”
Section: Moving Boundary Model For Distributary Channel Network: Mb_dcnmentioning
confidence: 99%